Using Improvement Science to Increase Accuracy and Reliability of Gestational Age Documentation - Kamath, Beena D.; Donovan, Edward F.; Christopher, Ronda; Brodbeck, Jennifer; Slone, Carolyn; Marcotte, Michael P. (American Journal of Perinatology, 2012)
Our aim was to improve the reliability of recording gestational age (GA) in the mother's obstetric record, as this record is used for clinical management, research databases, and eventual transmission to the Ohio Department of Health birth certificates. We performed a prospective cohort study, including all hospital births. We began quality improvement interventions in October 2009. Improvement test cycles were targeted to four working groups, including nursing staff, community obstetric providers, and the process itself. Test cycle results were evaluated to determine which successful interventions could spread further. Rates of process outcome measurements were compared by statistical process control and univariate analysis pre- and postintervention. During the preintervention period, the median daily GA reliability was 25%. To date, over 30 small sample size tests of change have been completed. Of 8795 births studied, significant improvement in GA accuracy/completeness was detected (median postintervention = 78%, p < 0.01). Increased communication of and completion of the prenatal record, in addition to GA recording in high-risk groups, such as premature infants, were also achieved (all p < 0.01). GA reliability can be increased using standardized improvement science methods. Better communication of GA will enable better clinical decisions and foster population-based perinatal research.
Keywords: gestational age; electronic medical record; birth certificate; vital statistics; quality improvement